Os limites de gestão e monitoramento da biodiversidade em unidade de conservação: o caso do Parque Nacional Montanhas de Tumucumaque (Brasil-Guiana Francesa) - CORDEIRO, Edileida Batista (2022)
Biodiversity studies represent a great challenge to the scientific community, especially when it comes to an area between two Pan-Amazonian countries that is prone to conflicts among gold miners, bio pirates, traffickers, farmers, indigenous peoples and the local community, mainly through the commitment assumed by Brazil under the Convention on Biological Diversity. This article seeks to analyze the constraints regarding management and monitoring of the biodiversity of the Tumucumaque Mountains National Park. The methodology used involved a bibliographical review and a survey in the context of a mixed methods approach. The results confirm a difficulty and presence of obstacles to effectively manage and monitor biodiversity.